Creation of a rigid host framework with optimum crystal structure and interface for zero-strain K-ion storage - Zhu, Yun-Hai; Wang, Jia-Zhi; Zhang, Qi; Cui, Yang-Feng; Huang, Gang; Yan, Jun-Min; Zhang, Xin-Bo (Energy & environmental science, 2022)
Potassium-ion batteries (KIBs) have gained considerable attention for stationary energy storage devices due to their low cost, natural abundance, and high energy density. However, owing to the significant strain caused by the accommodation of K ions, the diffusion of large K ions into conventional host frameworks inevitably causes sluggish diffusion kinetics or even structural failure during repeated K-ion insertion/extraction. Herein, to counter the mismatched relationship between the large K ions and compact host structures, we propose a new host design strategy that combines crystal engineering with interface engineering. Taking layered KTiNbO 5 (KTNO) as an example, favorable and stable K-ion diffusion channels are constructed in the rigid host through topologically converting layered KTNO into tunnel-structured Ti 2 Nb 2 O 9 (TNO) that stores K ions in a zero-strain way. Additionally, to overcome the limitation of K-ion storage sites inside a crystal, TNO is then exfoliated into nanosheets and further in situ coated with a highly graphitized carbon layer (CTNO). The resultant heterogeneous interfaces compensate for the unsaturated coordination environment of the TNO external surface and consequently provide abundant K-ion storage sites. Benefiting from the tailored crystal structures and heterogeneous interfaces, CTNO exhibits high reversible capacity (∼205 mA h g −1 ), excellent rate capability (∼72% capacity retention at 8 A g −1 ), and remarkable lifespan (∼100% capacity retention across nearly 10 000 cycles). These findings demonstrate the great potential of CTNO as a KIB material and provide insights into host design for achieving fast K-ion storage toward practical applications. Crystal engineering coupled with in situ interface engineering built a robust host for large K-ion storage, enabling a long cycle life of nearly 10 000 cycles without obvious capacity degradation.